Intrahippocampal injection of TsTX-I increases the levels of INF-γ in the cerebral tissue but not the levels of glutamate. (1st September 2015) - Rodriguez, Renan Volner; Dorce, Valquiria Abrão Coronado; de Freitas, Lucas Alves; Dorce, Ana Leticia Coronado; Lebrun, Ivo; Sobral, Ana Claudia Martins; Portaro, Fernanda Calheta Vieira; Kuniyoshi, Alexandre Kazuo; Carvalho, Daniela Cajado; Nencioni, Ana Leonor Abrahão
Abstract: TsTX-I, isolated from Tityus serrulatus scorpion venom, causes epileptic-like discharges when injected into the central nervous system. The involvement of excitatory amino acids and cytokines in this activity was investigated. Our results have demonstrated that TsTX-I increases the release of IFN-γ but does not alter the intracerebral concentration of the excitatory amino acids in rats. Thus, this cytokine seems to be more important in the convulsive process than glutamate. Highlights: TsTX-I increases the level of INF-γ in the brain and in the hippocampus. INF-γ may be involved in the convulsive effect of TsTX-I. Intrahippocampal levels of glutamate, glycine and GABA are not altered by TsTX-I. Intracerebral levels of IL-1α, IL-1β and IL-10 are decreased by TsTX-I.